2012
DOI: 10.2478/v10102-012-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of 2-PAMCl, atropine and curcumin against dichlorvos induced toxicity in rats

Abstract: The effect of 2- pyridine aldoxime methyl chloride (2-PAMCl) and atropine with or without curcumin was investigated in dichlorvos (2,2-dichlorovinyl dimethyl phosphate; DDVP) induced toxicity in rats. Rats were exposed to DDVP (2 mg/kg sub-cutaneously) once daily for the period of 21 days. Post DDVP exposure, rats were further treated with 2-PAMCl (50 mg/kg intramuscular, once daily) + atropine (10 mg/kg, i.m. once daily) with or without curcumin (200 mg/kg; oral; once daily) for further 21 days. We observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
(30 reference statements)
2
15
0
1
Order By: Relevance
“…Although several antidotes are available in the management of OP toxicity, the available options have some limitations with unavoidable side effects [8]. Therefore, the search for new and novel therapeutic drugs for OP poisoning is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Although several antidotes are available in the management of OP toxicity, the available options have some limitations with unavoidable side effects [8]. Therefore, the search for new and novel therapeutic drugs for OP poisoning is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…The histopathological alterations reported in this study are suggestive of degeneration and necrosis in the hepatocytes, cellular inflammatory responses leading to a sustained leakage of liver enzymes, and a burst in their level in the serum as seen in this study. The burden of OPs induced hepatotoxicity is not limited to its poisoning, but includes the limitations in the use of the available antidote (13). Nigella sativa used in the present study was observed to meliorate the hepatotoxicity activities of DDVP, by reducing the busted levels of the hepatic function enzymes (ALT, AST, ALP and GGT) in the rats that are exposed to only NSO and in those with prior exposure to DDVP.…”
Section: Discussionmentioning
confidence: 68%
“…It's toxicity have been associated with irreversible acetycholineesterase inhibition leading to acetylcholine accumulation, with clinical signs and symptoms well characterized to include lacrimation, salivation, bronchoconstriction, anoxia, and severe cardiac disturbances (12). Although, treatment of OPs poisoning involved routine use of several antidotes including atropine and pralidoxime chloride, they are without unavoidable limitations (13). Therefore, research into finding alternative regimen in the management of OPs poisoning is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…К тому же сочетание фармакологических агентов пилокар-пина, атропина применяли и в изучении феномена «окислительный стресс» [27,28].…”
Section: Aadsorasunclassified